AI AS NARRATIVE COMPANION: ENHANCING THE PHOTOVOICE METHOD FOR THE DEAF THROUGH HUMAN-AI COLLABORATION - Wibowo, Yosephien Reynalda Prananda (Telkom University, 2025)
Verbal communication can be extremely difficult for deaf people, so visual media and other forms of expression are crucial. The photovoice approach uses photography as an effective medium for expressing feelings and personal experiences. A participatory method called photovoice allows people to tell their stories through pictures, particularly in situations where words are insufficient. This study looks into how artificial intelligence (ChatGPT) might be used to help the deaf community during the photovoice narration stage. The study emphasizes AI's capacity to improve story structure, emotional depth, and clarity through a qualitative methodology that includes in-depth interviews and experimental comparison between self-written and AI-assisted narratives. The results indicate that participants respect their own expression, many also believe AI may help them articulate complex reflections and better organize their ideas. Participants recognized AI's value in enhancing storytelling, despite reservations about its often impersonal tone. Therefore, AI is most suited as a contemplative companion rather than a replacement, promoting diversity while maintaining the therapeutic and human centered of photovoice. This study adds to the growing body of knowledge regarding human-technology collaboration, specifically in the areas of inclusive, therapeutic, and creative communication practices for underserved groups.